2016
DOI: 10.21927/ijnd.2013.1(2).81-92
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan konsumsi buah dan sayur pada anak sekolah dasar yang obes dan tidak obes di Kota Yogyakarta dan Kabupaten Bantul

Abstract: Perbedaan konsumsi buah dan sayur pada anak sekolah dasar yang obes dan tidak obes di Kota Yogyakarta dan Kabupaten Bantul 81 Perbedaan konsumsi buah dan sayur pada anak sekolah dasar yang obes dan tidak obes di Kota Yogyakarta dan Kabupaten Bantul

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
2
0
6
Order By: Relevance
“…This result is in accordance with the research of Sartika (2011) which indicates the presence of meaningful relations between consumption patterns of fruits and vegetables with risk of obesity on 5-15 years children in Indonesia. The same with the research of Nuraeni (2013) indicates that school age children who obese are rarely and consume less fruits and vegetables compared with the child who is not obesity in Yogyakarta and Bantul. Children that rarely and consume less fruits and vegetables can increase the risk of obesity.…”
Section: Discussionsupporting
confidence: 78%
“…This result is in accordance with the research of Sartika (2011) which indicates the presence of meaningful relations between consumption patterns of fruits and vegetables with risk of obesity on 5-15 years children in Indonesia. The same with the research of Nuraeni (2013) indicates that school age children who obese are rarely and consume less fruits and vegetables compared with the child who is not obesity in Yogyakarta and Bantul. Children that rarely and consume less fruits and vegetables can increase the risk of obesity.…”
Section: Discussionsupporting
confidence: 78%
“…The survey team administered detailed structured questionnaires to cases and controls, as well as their parents, to collect data on sedentary behavior, fruit and vegetable intake, and junk food intakes. The design of this study has been reported elsewhere [15,26,32].…”
Section: Case-control Selectionmentioning
confidence: 99%
“…Fruit and vegetable intakes are inversely associated with overweight and obesity [12][13][14]. We have previously reported that obese school-aged children in Indonesia had a lower fruit and vegetable intake than non-obese children [15]. A systematic review suggested that adequate fruit and vegetable intakes may lower the risk of becoming obese [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pada siswa dengan jumlah konsumsi sayur dan buah kurang dari 5 porsi/hari mempunyai peluang berisiko menjadi obesitas sebesar 3,94 kali jika dibandingkan dengan siswa yang konsumsi lebih dari 5 porsi/hari. 24 Konsumsi sayur dan buah pada anak dipengaruhi secara signifikan oleh pengetahuan anak, pendidikan orangtua, dan ketersediaan pangan. 25 Meningkatkan jumlah porsi yang disajikan bisa menjadi salah satu alternatif untuk meningkatkan asupan sayur dan buah.…”
Section: Gambar 1 Jumlah Sisa Sayur Dan Buah Pada Makan Siang Sekolahunclassified